Numerical Study of the Effects of the Primary Air/Secondary Air Ratio and Coal Quality on Combustion Characteristics and Emissions in a 115 MW CFB Power Plant - Rahmad Syahrial; Wawan Aris Widodo (Green Publisher Indonesia, 2026)
The distribution of combustion air in a Circulating Fluidized Bed (CFB) boiler plays an important role in determining combustion performance and emission formation. Variations in coal quality result in differences in combustion characteristics, making it necessary to optimize the Primary Air/Secondary Air (PA/SA) ratio. This study aimed to analyze the effects of PA/SA ratio variations and coal quality on temperature distribution and exhaust gas composition in a 115 MW CFB power plant. The simulation was conducted using Computational Fluid Dynamics (CFD) with Ansys Fluent 2024 R2 software, incorporating PA/SA ratio variations of 40/60, 50/50, 60/40, and 70/30 for two coal types: Low-Rank Coal (LRC) and Medium-Rank Coal (MRC). The analyzed parameters included temperature distribution and mass fractions of CO₂, O₂, and NOx. The simulation results showed that PA/SA ratios of 40/60 and 50/50 produced more homogeneous temperature distributions compared with the 60/40 and 70/30 ratios. MRC produced higher furnace temperatures than LRC but also resulted in increased NOx emissions. The highest CO₂ mass fractions were obtained at PA/SA ratios of 40/60 and 50/50, with values of approximately 0.16–0.17, indicating more effective carbon conversion. An increase in the primary air ratio increased the concentrations of O₂ and NOx in the furnace. Overall, the 50/50 PA/SA ratio provided the optimal combustion performance, characterized by a more homogeneous temperature distribution, high carbon conversion efficiency, and controlled NOx emissions.